Value Chain Map of Small Agricultural Product-Processing Enterprises in Bandung, Indonesia - Endang Chumaidiyah (International Journal of Supply Chain Management, 2017)
Generally, informal small enterprises are still conventional in operating their business in view of some aspects, such as production and marketing, particularly from the side of value chain they create. This applies to small and micro processed food enterprises in Bandung Regency, of which more than 90 percent are informal enterprises with still low product values. Value chain analysis is an analysis of the activities that produce values, originating from both inside and outside the enterprises. The objective of the present research is to map the value chain of the entire activities undertaken by processed food enterprises. This value chain analysis approach is used to enhance the capacity of small enterprises by reviewing the whole value chain as a system. The value chain mapping provides clearness on which activities to enhance internally and externally in relation to other entities like suppliers, distributors, and consumers. The result of value chain map identified detail potential and barrier of SME Food Processing which be utilized as a solution for increased productivity, quality, and local value added as viewed from the entire activities, both internal and external.